2016
DOI: 10.1007/s10571-016-0423-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SHANK3 in the Temporal Neocortex of Patients with Intractable Temporal Epilepsy and Epilepsy Rat Models

Abstract: SH3 and multiple ankyrin (ANK) repeat domain 3 (SHANK3) is a synaptic scaffolding protein enriched in the postsynaptic density of excitatory synapses. SHANK3 plays an important role in the formation and maturation of excitatory synapses. In the brain, SHANK3 directly or indirectly interacts with various synaptic molecules including N-methyl-D-aspartate receptor, the metabotropic glutamate receptor (mGluR), and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor. Previous studies have shown that Autis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Mutations in gephyrin, an essential core scaffolding protein, have been demonstrated to be involved in the regulation of inhibitory PSD associated with pharmacoresistant epilepsy 38 . Furthermore, the alternative expression of the microtubule units (α‐ and β‐tubulin) and components (SH3 and multiple Ankyrin repeat domains 3, and postsynaptic density protein‐93) of PSD in excitatory neurons has been revealed in latent and chronic epilepsy 39–41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in gephyrin, an essential core scaffolding protein, have been demonstrated to be involved in the regulation of inhibitory PSD associated with pharmacoresistant epilepsy 38 . Furthermore, the alternative expression of the microtubule units (α‐ and β‐tubulin) and components (SH3 and multiple Ankyrin repeat domains 3, and postsynaptic density protein‐93) of PSD in excitatory neurons has been revealed in latent and chronic epilepsy 39–41 …”
Section: Discussionmentioning
confidence: 99%
“…38 Furthermore, the alternative expression of the microtubule units (α-and β-tubulin) and components (SH3 and multiple Ankyrin repeat domains 3, and postsynaptic density protein-93) of PSD in excitatory neurons has been revealed in latent and chronic epilepsy. [39][40][41] Homer scaffolding proteins (Homer1-3) are evolutionarily conserved key components of the PSD. Homer 1 is highly expressed in the cortex 42 and hippocampus, 43 which are regions associated with the etiology of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we explored the expression patterns of GIPC1 in the brain tissues of patients with TLE and mice with KA-induced epilepsy and our experimental results of reduced GIPC1 also show the possible involvement of GIPC1 in epilepsy. In addition, it has been reported that gene mutations in the GIPC protein family may be associated with the development of myoclonus, primary tremor, and juvenile epilepsy, 14 and previous studies have indicated that many scaffolding proteins [15][16][17] are involved in epilepsy; hence, we speculate that GIPC1 also participates in epilepsy.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, it has been reported that gene mutations in the GIPC protein family may be associated with the development of myoclonus, primary tremor, and juvenile epilepsy. 14 Furthermore, previous studies have indicated that many scaffolding proteins [15][16][17] are involved in epilepsy; hence, we speculate that GIPC1, a scaffolding protein, also participates in epilepsy. Through binding to various proteins, GIPC1 plays a role in many biological processes such as vesicular trafficking, 13,18 protein transport and expression, [19][20][21] endocytosis, 22 signal transduction, 23,24 and tumorigenesis.…”
Section: Introductionmentioning
confidence: 70%
“…More interestingly, recent evidence from human genetic studies also supports a role for SAPAPs in obsessive-compulsive behaviors [13,14]. Shank proteins are synaptic cytoskeleton-associated proteins that interact with SAPAPs, and previous studies identified a role for Shank3 in epilepsy [15][16][17] and indicate that PSD95/SAPAP/Shank multiprotein units might play an important role in organizing the postsynaptic signaling complex at glutamatergic synapses [18,19]. Few studies have investigated SAPAPs in the hippocampus; however, a previous study showed that SAPAP1, SAPAP2, and SAPAP4 transcripts are distributed in the cell body and that SAPAP3 is found in the molecular layers, which indicates that SAPAP3 may contribute to the function of dendritic spines in the hippocampus [20].…”
Section: Introductionmentioning
confidence: 88%